(untitled) (Baghdad Science Journal, 2004)
A number of ehemical ion materials were used as an absorber against solar energy. These materials were selected according to their absorption spectra in the wavelength range 300-800nm where the solar spectrum is coventrated. A solar olleetorw^esigd and The ability of each material inside the collector for absorbing the solar radiation was examined by a converter parameter “R”.According to the “R” parameter, the cohaltous and copperic ions material seems to be of higher capability for absorbing solar energy than the other materials.All the results were analyzed by means of a least-squared fitting program.